Evaluation of Attitude of Students toward Their Discipline and Its Relationship with Some Factors of Academic Failure in Students of Qom University of Medical Sciences in 2015 - Somayeh Momenyan; Akram Abedinipoor; Tahereh Seddighian; Leila Taheri (Zanjan University of Medical Sciences and Health Services, 2019)
Background & Objectives: Given the importance of attitude of students and its impact on their academic success or failure and with regard to the fact that attitude toward discipline is one of the factors affecting the academic status of students, this study aimed to determine the attitude of students toward their discipline and its association with academic failure. Materials and Methods: This descriptive and analytical research was performed on 313 students selected via simple sampling. Data analysis was performed using Chi-square, independent t-test, ANOVA, and linear regression. In addition, P-value of 0.05 was considered. Results: In this study, there was a significant relationship between GPA and year of receiving a diploma (P<0.05). In addition, the difference of attitude between various disciplines was significant, in a way that the most positive attitude was toward medical sciences and dentistry while the most negative attitude was related to health (P<0.001). On the other hand, there was an association between paternal level of education and units passed (P=0.03). Overall, some factors of academic failure had a relationship with the total score of attitude, in a way that the more positive the attitude, the less the academic failure (r=-0.33, P<0.001). Conclusion: According to the results of the study, the most positive attitude was related to the disciplines of medical sciences and dentistry, whereas the most negative attitude was toward the field of health. In this regard, there was a significant association between attitude and some factors of academic failure. Therefore, it is necessary to design and implement programs to improve the attitude of students toward their discipline and factors involved in academic success.